2022
DOI: 10.1177/26335565221123990
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between multimorbidity and composite lifestyle status in Shenzhen, China

Abstract: Objective The study aimed to understand multimorbidity among adults in a high-tech city in southern coastal China that has undergone rapid economic development and to investigate its relationship with lifestyle status. Methods A population-based survey was conducted among 24 community centers in the Nanshan District of Shenzhen from February to December of 2018. Participants were recruited using a stratified random sampling approach. A self-administered questionnaire on typical chronic diseases, lifestyle fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In this study, we identified 14 common chronic diseases based on the most frequently mentioned diseases for multimorbidity measures in previous studies (7,(9)(10)(11). Hypertension was defined as an average SBP of ≥140 mmHg and/or an average DBP of ≥ 90 mmHg, or self-reported hypertension history.…”
Section: Definition and Measurement Of Multimorbiditymentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we identified 14 common chronic diseases based on the most frequently mentioned diseases for multimorbidity measures in previous studies (7,(9)(10)(11). Hypertension was defined as an average SBP of ≥140 mmHg and/or an average DBP of ≥ 90 mmHg, or self-reported hypertension history.…”
Section: Definition and Measurement Of Multimorbiditymentioning
confidence: 99%
“…Moreover, some studies have revealed that variations in the prevalence and pattern of multimorbidity might be attributable to lifestyle and environmental factors. However, most studies on lifestyle factors and multimorbidity have been conducted in Western countries, where the multimorbidity pattern may differ from that in the Chinese population ( 7 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle risk factors which one can alter by avoiding unhealthy diet, physical inactivity, exposure to tobacco smoking, excessive consumption of alcohol, sleeping irregularities etc. [ 21 , 22 ] & [ 23 ]. Apart from, Education, Working status, marital status, household’s wealth quintile, residential place, religion, caste etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recently, many investigations have been conducted to explore the correlations of combined lifestyle factors (usually measured as lifestyle scores/indices) with various NCDs including MetS [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. For instance, a Spanish cohort study devised a nine-item lifestyle score and revealed an inverse association with MetS [ 28 ].…”
Section: Introductionmentioning
confidence: 99%